Prevalence, Haemato-Biochemical Changes and Pathology of Colibacillosis in Slaughtered Goats - Sunil Gaikwad, Sneha; Singh, Shailendra; Kumar Patel, Shailesh; Kiran Niranjan, Ankush; Shrivastava, Neeraj (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study aimed to investigate the prevalence, risk factors and pathological changes in intestine of slaughtered goats affected with  colibacillosis in Rewa districts of Madhya Pradesh. In this study, out of a total of 305 goats examined from different slaughter houses of  Rewa district 108 goats showing intestinal lesions were included for further study. Of the 108 intestinal contents collected, 33 (30.55%)  cases were found positive for the E. coli infection. The age-wise prevalence of colibacillosis was higher in 6-12 month of age (33.87%)  and decreased with advancement of age. Sex wise higher prevalence was found in female goats (36%) than males (28.91%). Goats  with colibacillosis had significantly lower level of haemoglobin and lymphocyte count, and significantly higher levels of PCV, TLC, TEC,  neutrophils and eosinophils. Biochemical analysis showed significantly lower level of sodium and higher level of potassium and alkaline  phosphatase in colibacillosis affected goats. Thirty three slaughtered goats that were positive for colibacillosis based on microscopic  examination included, catarrhal enteritis (9), haemorrhagic enteritis (6), necrotizing enteritis (8), necro-haemorragic enteritis (6), and  fibrinous enteritis (4).
Keywords: Colibacillosis; Goats; Haemato-biochemical profile; Pathomorphology; Prevalence